Comparison of scoring profile and game related statistics of the two finalist during the different stages of the 2011 Rugby World Cup - Vaz, L.; Vasilica, I.; Kraak, W.; Arrones, L. S. (International Journal of Performance Analysis in Sport, 2015)
The purpose of this study was compare the scoring profile and game related statistics of the two finalist during the different stages of the 2011 Rugby World Cup. The design of the study was descriptive and observational. The video recordings of all games that involved New Zealand and France during RWC 2011 (n=12 matches) were used and analyzed. The data were collected from the official web page of RWC (www.rugbyworldcup2011.com) and from the Rugbystats webpage (http://www.rugbystats.com.au). Results from game related statistics between New Zealand and France in RWC 2011, revealed different measures of performance for both teams. The main findings of the study show that New Zealand points mostly came from tries and France scored their points from penalty kick indicating the difference in approach by the two teams. The study revealed significant differences in performance indicators when comparing New Zealand and France rugby teams.